Developing Performance Assessment Instruments to Measure 4C Skills in Online Discussion Activities of Science Learning - Yuyun Maryuningsih; Topik Hidayat; Riandi Riandi; Nuryani Rustaman (Scientiae Educatia: Jurnal Pendidikan Sains, 2020)
The 21st century learning utilizes information technology for various activities, including online discussion forums, to increase students’ learning activities and learning interaction. The 4C’s performance assessment instrument in the online discussion forum is not yet available, thus, a 4C’s assessment, including communication, collaboration, critical thinking, and innovative creative thinking skills, is necessary to assess students’ performance in the process of online discussion activities. This research aims to develop 4C’s performance assessment instruments in the online discussion process using the ADDIE model. Meanwhile, instrument development included analysis, design, development, implementation, and evaluation. The instruments were in the form of observation sheets and assessment rubrics. This study tested 4C’s observation instruments in 104 students in online discussion activities during four online discussion activities. Data analysis included construct validity and reliability of each instrument indicator. The data analysis reveals that the 4C’s performance instruments are useable to measure students’ 4C’s skills in online discussion forums.